Understanding public awareness and knowledge of lung cancer screening practices: a cross-sectional study from the Asir region, Saudi Arabia - Kandasamy, Geetha; Orayj, Khalid; Alshahrani, Asma M.; Alanazi, Tahani S.; Hmlan, Amjad; Alharthi, Sitah; Alyami, Hanan; Khaled, Arwa (Frontiers in Public Health, 2025)
BackgroundLung Cancer (LC) remains one of the leading causes of cancer-related deaths globally, primarily due to late-stage diagnosis and inadequate public awareness of early symptoms and available screening methods. In Saudi Arabia, rising smoking rates and environmental risks increase the burden, particularly in regions like Asir. This study assesses public knowledge and awareness of LC symptoms, risk factors, and screening practices in the Asir region.MethodsA cross-sectional online survey was conducted from April to June 2025 among adults (≥18 years) in the Asir region, Saudi Arabia. Using convenience sampling, 437 participants completed a validated Arabic questionnaire assessing demographics, knowledge of LC symptoms and risk factors, and awareness of screening practices. Multivariable logistic regression identified factors significantly associated with knowledge levels (p < 0.05).ResultsOut of 437 participants, only 192 (43.9%) demonstrated good knowledge of LC, while the majority 245 (56.1%) had poor knowledge. Symptom awareness varied, with shortness of breath 277 (63.5%) most commonly identified, while frequent chest infections 198 (45.3%) and shoulder pain 129 (29.5%) were less recognized. Only 212 (48.5%) knew of screening methods, though 267 (61.1%) acknowledged the importance of early detection. Logistic regression showed significantly lower odds of good knowledge among high school graduates (OR = 0.242, 95% CI: 0.133–0.440, p < 0.001), diploma holders (OR = 0.120, 95% CI: 0.061–0.230, p < 0.001), and uneducated individuals (OR = 0.435, 95% CI: 0.215–0.870, p = 0.020) compared to degree holders. Employed participants (175; 40.0%) were more likely to have good knowledge than students (OR = 5.384, 95% CI: 2.650–10.939, p < 0.001). Those with smoker exposure among family/friends 228 (52.2%) had lower knowledge (OR = 0.382, 95% CI: 0.237–0.613, p < 0.001).ConclusionThis study highlights insufficient public knowledge of LC in the Asir region, with only 43.9% demonstrating good awareness. While smoking was widely recognized as a major risk factor, awareness of asbestos exposure, chronic obstructive pulmonary disease (COPD), and environmental pollutants was limited, and recognition of less common symptoms was often poor. Knowledge levels were significantly influenced by education, employment, and exposure to smokers. The findings highlight a critical need for targeted educational campaigns and awareness initiatives, particularly among less educated and high-risk populations, to promote early detection and reduce LC burden in the region.